A safe breeding ground: genetically improved maritime pine for growth and stem form has more efficient but not more vulnerable xylem. (20th October 2022) - Song, Yanjun; Bouteiller, Xavier Paul; Larter, Maximilian; Plomion, Christophe; Sin, Fabrice; Delzon, Sylvain
Abstract: Through repeated cycles of selection and recombination, tree breeding programs deliver genetically improved varieties for a range of target characteristics such as biomass production, stem form, resistance to biotic stresses, wood properties, etc. However, in the context of increased drought and heat waves, it is not yet known whether growth performance will impede drought resistance. To address this question, we compared the hydraulic properties, such as hydraulic efficiency and hydraulic safety, in four varieties over successive varieties of genetically improved maritime pines (i.e., Pinus pinaster Aït.) for growth and stem form. We measured 22 functional traits related to hydraulic efficiency, hydraulic safety, xylem anatomy and wood density. We found that improved varieties presented higher hydraulic conductivity with larger tracheid lumen size and tracheid lumen fraction, and smaller wall thickness reinforcement and tracheid density, but not at the cost of reduced embolism resistance. The reported absence of trade-off between hydraulic conductivity and embolism resistance is a strong asset to improve biomass productivity, through increased hydraulic efficiency, without impacting drought resistance, and should enable new maritime pine varieties to cope with a drier climate. Our study is one of the first to reveal the hydraulic mechanisms over successive varieties of genetic improvement for tree growth. It provides guidelines for sustainable forest management through breeding for other forest tree species. Abstract : One sentence summary Artificial selection in a pine tree enhanced hydraulic conductivity.